Pengaruh Pendapatan, Literasi Keuangan Dan Teknologi Keuangan Terhadap Perilaku Manajemen Keuangan Mitra GoCar Di Kota Kediri - Damayanti, Febry Aulia; Widodo, Eko; Laksono, Sonny Subroto Maheri (Otonomi, 2024)
Until 2022 and 2023, Gojek remains superior in the online transportation market in Indonesia. Gojek is an opportunity for business partners to develop their business and generate more economic benefits. Partners' financial management abilities are very necessary, in managing income and expenses, financing, saving and investing (Hilgert & Hogarth, 2003). The purpose of this research is to determine the significance or how much influence Income, Financial Literacy and Financial Technology both partially and simultaneously have on the Financial Management Behavior of GoCar Partners in Kediri. This research includes quantitative research that produces discoveries using statistical procedures. Primary data had taken using the questionnaire method, found 91 samples from the entire population using the purposive sampling method. Based on the results of the partial T Test, Income, Financial Literacy and Financial Technology each partially have a positive and significant effect on the Financial Management Behavior of GoCar partners in Kediri. From the results of the Simultaneous F Test, it is found that Income, Financial Literacy and Financial Technology simultaneously have a positive and significant effect on the Financial Management Behavior of GoCar partners in Kediri. This shows that income level, financial knowledge and ability to use financial technology together can influence a person's ability to organize, plan, manage, control and save finances in everyday life.